Analisis Perbedaan Perilaku Keuangan antara Mahasiswa dan Mahasiswi di Kota Jember - Wardatun, Vita; Hafidzi, Achmad Hasan; Puspitadewi, Ira (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Financial problems are caused by individual’s who do not understand financial knowledge and have bad financial management habits. Weak money management can affect behavior, thus making college and female college students more sensitive to financial crises (Rai et al, 2019). The purpose of this study was to determine and examine the variation in financial behavior between male students and female students in Jember city. The research used is comparative research with a quantitative approach. This study will see whether there are differences in financial behavior between male students and female students in Jember city. Based on the findings of this study, there are differences in financial behavior between students and female students in the city of Jember. The novelty in this research lies in the object used in this study by eight university, besides that it lies in the variable, namely financial behavior. Keywords: Financial Behavior, Gender